Spare Parts Support Optimization Algorithm Based on Support Degree - Jian-jun Gao; Li-qiang Jiang; Qiang Guo; Jin-cheng Han; Rui-feng Zhao; Chun wang (Institute of Advanced Engineering and Science, 2013)
we consider the actual situation of wartime equipment support and the different life of the old and new spare parts, in-depth analyze the impact of spare parts scheduling on the support degree, and establishe support degree model of the three-levels spare parts scheduling. According to the characteristics of the model, the introduction of the classic scheduling algorithm for optimization of spare parts, can effectively improve the efficiency of support,the last example shows that the effectiveness of the method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3040